Two Theologies of Death: Anthropological Gleanings - Kelsey, David H. (Modern theology, 1997)
Theologies of death by Karl Rahner and Eberhard Jungel are closely analyzed to test the hypothesis that the coherence of Christian theological anthropology depends on holding in dialectical balance the implications of three distinct ways in which God relates to humankind (as creator, as redeemer and as eschatological consummator) held in dialectical equipoise. Connections are shown between Rahner’s focus on creation/consummation (subordinating the redemption-relation) and his unintended undercutting of sola gratia; and between Jungel’s focus on creation/redemption (subordinating consummation) and his evacuating the ontological status of the creature. Four positive morals are drawn for doing anthropology.